1994
DOI: 10.1139/z94-207
|View full text |Cite
|
Sign up to set email alerts
|

Wolf and bear predation on white-tailed deer fawns in northeastern Minnesota

Abstract: 1994. Wolf and bear predation on white-tailed deer fawns in northeastern Minnesota. Can. J. Zool. 72: 1557 -1565. White-tailed deer (0doc.oileus lir-ginianus) fawn mortality was studied during the summers of 1989 and 1990 in northeastern Minnesota. Estimated pooled mortality rates for 2 1 radio-tagged fawns were 0.44 for the May-June, 0.13 for the July-October, and 0.51 for the May-October intervals. Predation accounted for all mortalities, with wolves (Canis lupus) responsible for 5 1 % of them and black bear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 50 publications
13
129
3
Order By: Relevance
“…We coded calf fates through the first year of life as survivor, mortality, or censored. We evaluated mortality events following methods modified from those used by Garner et al (1985) and Kunkel and Mech (1994). We concluded that a carcass was scavenged if we determined no 1) evidence of subcutaneous hemorrhaging; 2) aspirated blood in mouth, nose, or trachea; or 3) signs of struggle including scuff or track evidence of chase and struggle, blood on the ground from pursuit, broken branches, or blood on plants.…”
Section: Investigating Mortality Sitesmentioning
confidence: 99%
“…We coded calf fates through the first year of life as survivor, mortality, or censored. We evaluated mortality events following methods modified from those used by Garner et al (1985) and Kunkel and Mech (1994). We concluded that a carcass was scavenged if we determined no 1) evidence of subcutaneous hemorrhaging; 2) aspirated blood in mouth, nose, or trachea; or 3) signs of struggle including scuff or track evidence of chase and struggle, blood on the ground from pursuit, broken branches, or blood on plants.…”
Section: Investigating Mortality Sitesmentioning
confidence: 99%
“…Wolves occurred throughout the study area at densities of 30-36/1,000 km 2 during the study (Mech 2009). White-tailed deer (Odocoileus virginianus) occurred at densities of 12-15/10 km 2 (M. H. Dexter, Minnesota Department of Natural Resources, unpublished report) and constituted the major prey of wolves in the area (Frenzel 1974;Mech 1981, 1986), primarily fawns during summer (Van Ballenberghe et al 1975, Nelson and Mech 1986, Kunkel and Mech 1994. Wolf packs inhabiting the area were the Campers Lake Pack, Isabella River Pack, Pike Lake Pack, and Stony River Pack.…”
Section: Study Areamentioning
confidence: 99%
“…remaining inhabited these zones (Hoskinson and Mech, 1976;Mech, 1977a, c;Nelson and Mech, 1981). Even after the deer population increased, we continued to find evidence of this relation (Kunkel and Mech, 1994). Buffer zones between territories of wolf packs are important to territorial maintenance.…”
Section: Territoriality Of Wolf Packsmentioning
confidence: 67%
“…Wolves tended to kill old deer Mech and Karns, 1977;Nelson and Mech, 1986a); deer with abnormalities (Mech and others, 1970;Mech and others, 1971;Mech and Karns, 1977); deer with low blood fat (Seal and others, 1978); deer with low marrow fat Mech, 2007); and newborn fawns of below-average weight and (or) with low serum urea nitrogen (Kunkel and Mech, 1994).…”
Section: Studies Of Deer Ecologymentioning
confidence: 99%